Anomalies and Specific Functions in the Clinical Identification of Defense Mechanisms. Issue 5 (27th March 2014) - Perry, J. Christopher
<x xml:space="preserve">Abstract</x> Standard teaching about defense mechanisms generally focuses on definitions, which do not readily aid the clinician in identifying defenses whenever individuals use them. This report demonstrates a process by which the clinician can identify when a defense is used, which ones are likely being used, and with what aim. Clinicians first notice that a defense may be operating whenever the other individual presents with anomalies in the expression of affect, behavior, speech, or its content. Some of these anomalies are described. Next, to identify the specific defense or general level of defensive functioning used, the clinician must identify the specific function of the defense in context using a process of guided clinical inference. This report examines 2 verbatim examples from recorded interviews of one case to demonstrate this process. The examples present a microcosm of clinical concerns that have a surprising relationship to the individual's course and prognosis.